Systemic conditions and treatments as risks to dental implant therapy - Arguedas Vega, Natalia (2014)
The aim of this article is to describe posible risks and considerations described in the scientific literature for osseointegration in patients with systemic conditions, medical treatments or smoking habit and complications for osseointegration of diseases and / or systemic treatments, as well as smoking. The search and review of the literature available was made in the EBSCO, Ovid, Science Direct, PubMed, databases covering, all human studies that report survival of implants placed in patients who have at least one of the conditions studied, as well as other risks associated to surgical procedures in the placement of implants including. In the literature up to November 2012. The studies found are case reports and case series. No studies have compared patients with and without systemic conditions in a controlled manner. The level of evidence indicating absolute and relative contraindications for implant therapy in patients with the systemic level is low. Study is required primarily for patients with a bisphosphonate regimen.